The Influence Of Audio Visual Media On Maharatul Istima' Arabic Language Subjects - Suhaimah (Business Finance Analyst Co., 2023)
The objectives of this research are: first, to determine the influence of audio-visual media in Arabic language subjects on Maharatul Istima' (Listening Skills) of class V MI Tarbiyatun Nasyiin 1 Grujugan Prohibition Pamekasan students; secondly, to find out the magnitude of the influence of audio-visual media in Arabic subjects on Maharatul Istima' (Listening Skills) of class V MI Tarbiyatun Nasyiin 1 Grujugan Prohibition Pamekasan students. This research is a type of research that uses a quantitative approach or method, which uses statistical data analysis. Meanwhile, its nature is correlation, namely looking for relationships between one variable and another variable. The population of this research was all class V students at MI Tarbiyatun Nasyiin 1. The data for this research was obtained by means of observation, distribution of questionnaires and documentation. The results of the hypothesis test analysis of the influence of audio-visual media on maharatul istima' show that a correlation coefficient of 0.552 is consulted in the r-table with N=17 and a significance level of 5%. The r-table value obtained is 0.482 so the calculated r-value is greater than r-table. So it can be concluded that Ho was rejected and Ha was accepted or it could be said that there was an influence from the use of audio-visual media in Arabic subjects on maharatul istima' (listening skills) of class V MI Tarbiyatun Nasyiin 1 Grujugan Prohibition Pamekasan students